Jururawat Mesra Ibadah - Anita, Abdul Rani; Aini, Ahmad (Penerbit UMP, 2014)
The book explains how nurses and caretakers can help patient perform ablution and prayer. The book also includes a spiritual guidance to enhance spiritual intelligence.